Electromyographic analysis of the discus standing throw - Peng, H.; Huang, C.; Peng, H. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this study was to compare the muscular activation in different discus weights and investigate the sequences and the patterns of the muscular function of the standing throws with discus. The surface EMGs of thirteen muscle groups were measured. The forearm flexor, triceps brachii, posterior deltoid and middle deltoid were highly activated muscle groups in the standing throws. The forearm flexor exerted the highest activation among thirteen muscle groups. The trapezius, pectoralis major, forearm muscle groups, biceps brachium, and anterior deltoid reached the peak EMG activities just before the discus was released. The posterior deltoid, middle deltoid, lower trapezius, and middle trapezius mainly supported the arm and the discus in the early part of the standing throws.